Implementasi Media Audio Visual dalam Meningkatkan Pemahaman Materi Akhlak Tercela padaMata Pelajaran Akidah Akhlak - Nurmisdaramayani Nurmisdaramayani; Muhammad Khalidin ; Sinta Triwindarti (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2020)
Media is a supporting tool in a learning process. Its existence is sufficient to help educators in delivering material to students. The use of this media can affect student learning outcomes related to their understanding of the material. Howener the reality that occurs in MTs Al-Banna on the island especially in grade VII in the subject of morals learning outcomes have not been maximized. This is because the learning process still uses classical methods without involving the use of media in it. Teacher more often use the lecture method which makes students tend to get bored and pay less attention. With this fact it is necessary to do internal innovation. The learning process includes the application of media in improving learning out comes as a measure of student understanding. On of them is audio visual media, the use of this media is avite fun with the collaboration between images and sound, so it will be suitable if used to convey story material accompanied by practice. This research was conducted using a classroom action research method that includes two cycles. Each cycle consists of 4 steps namely: planning, implementing, observing, and reflevting. The results of research conducted on MTs Al-Banna island show a lot of improvement. In cycle I the student learning outcomes were 64% and 36% incomplete, while in cycle II experienced a drastic increase, the number of student who had complete was 92% and those who had not completed were 8%.